The Tribology Behaviour of Polycarbonate Urethane (PCU) as Advance Material on Biomedic - Wahyu Dwi Lestari; Ndaru Adyono (Future Science)
End-stage osteoarthritis of the hip can be treated by replacing the joints using an artificial hip joint. Recent research states that polycarbonate urethane (PCU) can be used as an alternative bearing in UHMWPE material because of its better properties. This study aimed to determine the value of friction coefficient, the width of wear track, The volume of wear track, wear rate, and wear particle analysis. The method used is to test the wear of the PCU material using a pin on the disc tribometer machine. The wear test was carried out for 50,000 cycles with a loading of 500 grams and variations in speed (50 Rpm, 100 Rpm, 200 Rpm). The test is carried out in conditions without lubrication. The results of this study showed that the average friction coefficient of 50NL, 100 NL, and 200NL PCU discs were 0.114, 0.116, and 0.127, respectively. The width track values of the 50NL, 100 NL, and 200NL disc specimens were 2,679 mm, 4,168 mm, and 5,211 mm, respectively. The volumetric wear values of the 50 NL, 100 NL, and 200NL disc specimens were 76,428 mm3, 355,104 mm3, and 1049,328 mm3, respectively. The wear rate specimen disc values of 50NL, 100 NL and 200NL using the wear track calculation method were 1.352 x 10-3 mm3 / Nm, 6.283 x 10-3 mm3 / Nm, and 1.857 x 10-2 mm3 / Nm, respectively.